ANALISIS MAQASID SYARIAH AL-SYATHIBI TENTANG KEWARISAN ANAK PEREMPUAN DALAM PERKAWINAN ADAT MISAN - Ita Rahmania Kusumawati; Fahrurrozi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the practice of daughters' inheritance in the customary misan (endogamous) marriage in the Ssasak Tribe's aristocratic community using the perspective of the maqasid sharia of Imam al-Syathibi. The main focus of this study is to analyze the legality of customary misan marriage and its implications for daughters' inheritance rights, particularly restrictions on access to the family's principal assets. This study uses a qualitative approach with a literature study combined with a conceptual normative analysis of customary law, Islamic inheritance law, and the concept of maqasid sharia in the book al-Muwafaqat. The results show that customary misan marriage does not conflict with Islamic law because it is not included in the category of prohibited marriages. The practice of limiting the inheritance rights of noble daughters is understood as a customary mechanism to maintain the honor, lineage, and family assets so that they remain within one kinship line. From the perspective of maqasid sharia, this practice can be categorized as an effort to maintain the public interest which is included in the dharuriyyat needs, even though it has individual consequences. Thus, the inheritance system in customary marriages can be accepted as long as it does not violate the principles of Islamic law and remains oriented towards the welfare of the community